A Case of Severe COVID-19 in a Patient with Acute Graft-versus-Host Disease after Haploidentical Transplantation - Dan Han; Yuqian Sun; Rong Xie; Xiaojian Zhu; Zhaodong Zhong (Case Reports in Hematology)
We report a case of coronavirus disease 2019 (COVID-19) after haploidentical transplantation with acute graft-versus-host disease (aGVHD). COVID-19 and aGVHD were improved under treatment with arbidol, remdesivir, methylprednisolone, and ruxolitinib. However, eventually, the patient died of septic shock and multiple organ failure. It was concluded that the disease condition of this COVID-19 patient after transplantation was serious, complex, and variable, with poor prognosis.